2023
DOI: 10.3390/medicina59101700
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Age Classification into Five-Year Intervals to Explain Sarcopenia and Immune Cells in Older Adults

Seung-Jae Heo,
Yong-Seok Jee

Abstract: Background and Objectives: This study focused on investigating sarcopenic factors and immune cells in older adulthood. To achieve this, the variables related to sarcopenia and immune cells in people living in the same community were analyzed. Materials and Methods: A total of 433 elderly individuals aged 61 to 85 years were randomly categorized as follows in 5-year intervals: 68 in the youngest-old group (aged 61–65), 168 in the young-old group (aged 66–70), 127 in the middle-old group (aged 71–75), 46 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…Previous studies have confirmed the association between inflammation and sarcopenia 30 , 33 , 67 , 68 . Seung Jae Heo et al found that the risk of sarcopenia increased significantly with every 5 consecutive years of age increase 88 ; our study showed that the risk of sarcopenia increased more significantly with the increase of SII values in the population aged 50–59 years. Yoo et al found that chronic inflammatory status in the elderly can cause inflammatory cytokines to antagonize the synthesis and metabolism of IGF-1, leading to muscle synthesis disorders 63 .…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies have confirmed the association between inflammation and sarcopenia 30 , 33 , 67 , 68 . Seung Jae Heo et al found that the risk of sarcopenia increased significantly with every 5 consecutive years of age increase 88 ; our study showed that the risk of sarcopenia increased more significantly with the increase of SII values in the population aged 50–59 years. Yoo et al found that chronic inflammatory status in the elderly can cause inflammatory cytokines to antagonize the synthesis and metabolism of IGF-1, leading to muscle synthesis disorders 63 .…”
Section: Discussionsupporting
confidence: 56%